Sosialisasi Pengelolaan Sampah Plastik Desa Jambidan - Pramesta Praba S (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasing productivity of waste use, especially in the form of plastic waste in urban areas, contributes greatly to environmental pollution because plastic waste takes a long time to decompose. People currently choose plastic as a food and beverage wrapper because it is more practical without knowing the impact or danger of plastic itself. Public knowledge of the dangers of plastic is still low. Therefore, socialization is needed about waste management, especially plastic waste. The purpose of socialization or education activities on the importance of waste management and ways to reduce, reuse, and recycle waste, especially plastic waste is to provide knowledge and increase public awareness to reduce plastic waste and know the dangers of plastic for health and the dangers of plastic waste in the environment. This waste management socialization activity explains about 3 ways of waste management, namely: Reduce, Reuse, and Recycle. With this activity, it is hoped that people will not litter and can manage waste properly.